A note on species identification in the genus Libycoceras Hyatt, 1900 (Ammonitina, Late Cretaceous) - Ifrim, Christina (Cretaceous research, 2018)
Species of the sphenodiscid genus Libycoceras are widely used for correlation of Campanian-Maastrichtian strata in West and North Africa and the Middle East (Levant). Five valid species are discussed herein, viz. L. crossense Zaborski, 1982, L. dandense (Howarth, 1965), L. afikpoense Reyment, 1955, L. acutodorsatus (Noetling, 1897) and L. ismaelis (von Zittel, 1884), the last named being the most widely cited. However, a systematic review of this species has shown that the holotype of this species is lost, and that many subsequent records were erroneous. Other species of Libycoceras are described briefly, inclusive of a discussion whether or not L. chargense (Blanckenhorn, 1900) could be regarded as a synonym of L. acutodorsatus. An identification key which lists the main features on which these five species can be differentiated is provided in order to enable correct assignment even by non-palaeontologists. On the basis of these adjusted taxonomic concepts, the five species of Libycoceras turn out to be suitable for long-distance correlation, in contrast to other coeval oxycone ammonites.